Perceived needs of stroke survivors at Kamuzu Central Hospital in Lilongwe district. - Chimseu, Witness (Kamuzu University of Health Sciences, 2022)
Stroke is the sudden death of some brain cells caused by lack of oxygen when the blood flow to the brain is impaired by blockage or rupture of an artery in the brain. The two common types of stroke are ischemic and hemorrhagic. Patient's progress during recovery depends on which side of the brain was affected and progress differs from one person to another. This study is about individuals who had stroke and survived (survivors). The purpose of the study is to explore the perceived needs of survivors post-stroke at Kamuzu Central Hospital, physiotherapy department. BROAD OBJECTIVE: To explore perceived needs of stroke survivors at Kamuzu Central Hospital. METHODOLOGY The study design to be used is qualitative, where in-depth interviews will be used to solicit information from the participants. A purposive sample of ten participants will be used. The participants in this study will be stroke survivors who have been attending rehabilitation services at KCH in Lilongwe. Malawi for more than four months and are able to speak. An interview schedule will be used for data collection. Data will be collected by the researcher and be recorded through writing and audiotapes to capture all the information from the respondents. The entire data collection will take place over a period of not less than 10 days. Content analysis will be used as a method of data analysis. After data collection, the recorded data tapes and written documents will be stored in a locked cupboard to ensure confidentiality. The data will only be accessible to the researcher. After analysis, the tapes and all the written documents will be kept in a locked cupboard for a maximum period of five years then discarded by burning.